Incidence and molecular basis of CD36 deficiency in Shanghai population. Issue 3 (21st October 2014) - Li, Ruishu; Qiao, Zhenglei; Ling, Bing; Lu, Ping; Zhu, Ziyan
<x xml:space="preserve">Abstract</x> Background CD36 is a multifunctional membrane receptor and is expressed in several cell lines. Individuals who lack platelet (PLT) CD36 are at risk for immunization against this antigen, leading to several clinical syndromes. This study aimed to investigate the frequency and molecular basis of CD36 deficiency in Shanghai. Study Design and Methods Whole blood samples were collected from healthy blood donors, and the PLTs and monocytes were analyzed using flow cytometry to determine CD36 deficiency type. After genomic DNA was extracted, Exons 3 to 14 of CD36 gene including a part of relevant flanking introns were amplified. Direct nucleotide sequencing and sequence alignment were performed. The samples that showed mutations were confirmed by clonal sequencing. Results Of the 1022 healthy blood donors analyzed, 22 individuals failed to express CD36 on PLTs; two of them expressed no CD36 on their monocytes either. These results demonstrated that the frequencies of Type I (lacking CD36 expression on PLTs and monocytes) and Type II (lacking CD36 expression on PLTs only) CD36 deficiency among the study population were 0.2 and 2.0%, respectively. Nucleotide sequencing analysis revealed nine different mutations including six mutations that were not yet reported. The most frequent mutations among the study population were 329‐330delAC and 1228‐1239delATTGTGCCTATT. Conclusion The study findings have confirmed the fact that the frequency of CD36 deficiency in the Chinese population is slightly lower than that in other Asian countries. The identification of several new mutation types indicated the polymorphism of CD36 gene in the Shanghai population.